Determinats of Fraud Prevention and Financial Performance as an Intervening Variable - Hendri, Hendri; Yuliantoro, Yuliantoro; Ama, Maksimilianus Kolot (International Journal of Economics and Financial Issues, 2019)
The purpose of this study was to analyze the role of financial performance in mediating the effects of the performance of human resources, internal controls, standard operating procedures and organizational culture to the prevention of fraud. The population of this study is 58 Unit School and all schools and Power Finance unit manager Tarakanita School unit in Indonesia amounting to 202 people. The sampling method using a purposive sampling method. Data were processed amounting to 142 data with the dataa processing method using the Smart PLS. Hypothesis testing results showed that the quality of human resources and a significant positive effect on financial performance. Internal controls and a significant positive effect on financial performance. Standard operating procedure positive and significant impact on financial performance. Organizational culture positive and significant impact on the financial performance ko. Financial performance and significant positive effect on the prevention of fraud. The quality of human resources and a significant positive effect on the prevention of fraud. Internal controls and a significant positive effect on the prevention of fraud. Standard operating prprocedures positive and significant effect on the prevention of fraud. The organizational culture had no effect on the prevention of fraud. The results of the analysis of mediating variables using the Sobel test found that financial performance is able to mediate the effect of the quality of human resources, internal controls, standard operating procedures and organizational culture to the prevention of fraud. Keywords: Quality of human resources, internal controls, standard operating procedures, organizational culture, prevention of fraud JEL Classifications: E10, E32, E60 DOI: https://doi.org/10.32479/ijefi.8955